Different Endurance Exercise Modalities, Different Affective Response: A Within-Subject Study - Dierkes, Katja; Mattioni Maturana, Felipe; Rösel, Inka; Martus, Peter; Nieß, Andreas M.; Thiel, Ansgar; Sudeck, Gorden (Frontiers in Psychology, 2021)
Affect experienced during an exercise session is supposed to predict future exercise behavior. However, empirical evidence reveals high variability in affective response to different exercise modalities. Thus, the purpose of the present study was to compare acute affective response and its variation during three different endurance exercise modalities: (a) moderate-intensity continuous exercise (MICE), (b) vigorous-intensity continuous exercise (VICE), and (c) high-intensity interval exercise (HIIE). Using the dual-mode theory as a theoretical framework, cognitive and interoceptive factors were considered as potential predictors of in-task affective response. In a within-subject design, 40 insufficiently active healthy participants (aged from 20 to 40 years) attended three sessions per exercise modality on a cycle ergometer. Affective valence (measured by the Feeling Scale), two cognitive factors (perceived competence and awareness of interoceptive cues), and one interoceptive factor (heart rate) were assessed before, during, and after each exercise session. Mixed models with three levels (subject, exercise session, and time point) revealed more positive affective valence during MICE compared with VICE (p < .001) and HIIE (p < .01), while there was no significant difference between the latter two. Levene’s test results showed the highest variability of in-task affective valence during VICE (ps < .01). Regarding the course across the session, MICE was associated with a constant slight increase in affective valence from pre- to post-exercise (p < .05), whereas VICE and HIIE caused a decline in pleasure (ps < .001), followed by an affective rebound immediately after exercise termination (ps < .01). The highest importance of cognitive and interoceptive factors for in-task affective valence was observed in VICE (ps < .05). The current findings provide support for the tenets of the dual-mode theory, however, indicating that there may be differences in the affect-intensity relationship between continuous and interval exercise. In conclusion, the study results concerning previously insufficiently active individuals extend the knowledge of how exercise can positively shape affective well-being depending on exercise modality and psychophysiological influences. This knowledge enables public health practitioners to design more individualized activity recommendations, thereby improving the subjective experience of exercise.